3r (Reuse, Reduce, Recycle) Education for Students in Pangauban Village as an Effort to Build Awareness About Waste Management from Early Ages - Hidayah, Tami Aspi Zahda; Nuragistiani, Ade Rini; Nurkamilah, Milah; Mujiarto, Mujiarto; Nugraha, Mohammad Fahmi; Nurfitriani, Meiliana; Nuryuniarti, Rissa; Saleh, Yopa Taufik; Sahroni, Oni; Husen, Wan Ridwan (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
In Pangauban Village there is a lot of garbage on the side of the road that accumulates and the majority of the population throws garbage into the Citarum river, causing an unpleasant odor. With this condition, it will certainly cause various problems such as waste problems because it is not managed properly and the behavior of throwing garbage into river areas is imitated by children so that it is considered a normal thing. Therefore, 3R (Reuse, Reduce, Recycle) Education activities were held for Elementary School and PAUD students in Pangauban Village, with the aim of changing mindsets and adding insight into waste management and utilization to foster environmental care characters from an early age. 3R (Reuse, Reduce, Recycle) education is carried out by means of presentations using Power Point, showing animated videos and by bringing samples of types of waste and the work that has been made from waste. After conducting 3R Education (Reuse, Reduce, Recycle) there were some changes that were felt, namely that the majority of students had more understanding and awareness about how to treat waste properly